Electrospun Nanofibrous Poly (Lactic Acid)/Titanium Dioxide Nanocomposite Membranes for Cutaneous Scar Minimization - Marsi, Teresa C. O.; Ricci, Ritchelli; Toniato, Tatiane V.; Vasconcellos, Luana M. R.; Elias, Conceição de Maria Vaz; Silva, Andre D. R.; Furtado, Andre S. A.; Magalhães, Leila S. S. M.; Silva-Filho, Edson C.; Marciano, Fernanda R.; Zille, Andrea; Webster, Thomas J.; et al. (Frontiers in Bioengineering and Biotechnology, 2019)
Poly (lactic acid) (PLA) has been increasingly used in cutaneous tissue engineering due to its low cost, ease of handling, biodegradability, and biocompatibility, as well as its ability to form composites. However, these polymers possess a structure with nanoporous that mimic the cellular environment. In this study, nanocomposites are prepared using PLA and titanium dioxide (TiO2) (10 and 35%—w/w) nanoparticles that also function as an active anti-scarring agent. The nanocomposites were prepared using an electrospinning technique. Three different solutions were prepared as follows: PLA, 10% PLA/TiO2, and 35% PLA/TiO2 (w/w%). Electrospun PLA and PLA/TiO2 nanocomposites were characterized morphologically, structurally, and chemically using electron scanning microscopy, transmission electron microscopy, goniometry, and X-ray diffraction. L929 fibroblast cells were used for in vitro tests. The cytotoxic effect was evaluated using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assays. Versicam (VCAN), biglicam (BIG), interleukin-6 (IL6), interleukin-10 (IL-10), and type-1 collagen (COL1A1) genes were evaluated by RT-qPCR. In vivo tests using Wistar rats were conducted for up to 15 days. Nanofibrous fibers were obtained for all groups that did not contain residual solvents. No cytotoxic effects were observed for up to 168 h. The genes expressed showed the highest values of versican and collagen-1 (p < 0.05) for PLA/TiO2 nanocomposite scaffolds when compared to the control group (cells). Histological images showed that PLA at 10 and 35% w/w led to a discrete inflammatory infiltration and expression of many newly formed vessels, indicating increased metabolic activity of this tissue. To summarize, this study supported the potential of PLA/TiO2 nanocomposites ability to reduce cutaneous scarring in scaffolds.